(untitled) (Хабаршы. Психология және социология сериясы, 2022)
In the conditions of rapid changes taking place in the socio-economic life of Kazakhstan, much attention is paid to young people who are gradually taking active positions in the economic, political, and cultural spheres. Young people are aimed at developing and promoting their initiatives, mainly starting to implement them during the professional training. In these conditions, the socio-cultural potential of the youth acts as a combination of qualities and capabilities of the younger generation, formed under the influence of certain factors and a professionally oriented educational environment. From this perspective, we should determine these factors in accordance with the realities of modern times and youth’s point of view. The purpose of the research was to determine the structure of significant indicators for youth’s socio-cultural potential development in the context of professional education via the free-associative method. It was considered how the different categories of respondents react to the incentive words and phrases such as "youth", "youth’s socio-cultural potential", "socio-cultural environment", and "cross-cultural interaction". Interpretation of the obtained results allows us to divide associations based on keywords and the repeatability sums values of the mentions into groups that make up the semantic core for each definition. As a consequence, twenty cognitive paradigmatic signs with a positive connotation were identified. The scientific value and novelty of the work arrows in proving the possibility of using the free-associative method for the definition of the logical components of the concepts in accordance to the ideas of a certain social group about it. The main conclusions of the research confirm that the youth of Kazakhstan, as a social group, has a formed structure of associations regarding the role and status of youth in society and the development of socio-cultural potential, including in conditions of intercultural interaction. The practical significance of the results provides a base for the determination of the socio-cultural potential of youth indicators in the professional study field. Key words: associative method, frequent reactions, semantic core, socio-cultural interaction, youth.